Fine-Tuning Stomatal Movement Through Small Signaling Peptides - Qu, Xinyun; Cao, Bing; Kang, Jingke; Wang, Xuening; Han, Xiangyu; Jiang, Wenqian; Shi, Xiong; Zhang, Luosha; Cui, Langjun; Hu, Zhubing; Zhang, Yonghong; Wang, Guodong (Frontiers in Plant Science, 2019)
As sessile organisms, plants are continuously exposed to a wide range of environmental stress. In addition to their crucial roles in plant growth and development, small signaling peptides are also implicated in sensing environmental stimuli. Notably, recent studies in plants have revealed that small signaling peptides are actively involved in controlling stomatal aperture to defend against biotic and abiotic stress. This review illustrates our growing knowledge of small signaling peptides in the modulation of stomatal aperture and highlights future challenges to decipher peptide signaling pathways in guard cells.